1994
DOI: 10.1159/000147552
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Lens in Human Embryos: A Histochemical and Ultrastructural Study

Abstract: The early development of the lens was examined, using 36 externally normal human embryos at Carnegie stages 13–23 (4 to 8 weeks of gestation). Twenty-two embryos were sectioned serially and stained with periodic acid-Schiff and a modified method of PAS. In 14 embryos, not only the differential distribution of glycogen but also the ultrastructural change in the developing lens, with special reference to junctional complexes, were examined electron microscopically. At stage 15, when the lens vesicle was formed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ophthalmic Res 1996:28:270-274 vesicle in a stage-15 human embryo; however, aA-and aB-crystallin were observed over nearly the entire area of the lens vesicle [6], We previously reported that glycogen ap peared in the posterior portion of the lens ves icle at stage 15 [19], Therefore, the distribu tion of HSP28 in the lens vesicle at stage 15 was similar to that of glycogen rather than that of aB-crystallin. In the present study, HSP28 appeared in the anterior lens epithelium at stage 19.…”
Section: Hsp In the Lenses Of Human Embryosmentioning
confidence: 85%
“…Ophthalmic Res 1996:28:270-274 vesicle in a stage-15 human embryo; however, aA-and aB-crystallin were observed over nearly the entire area of the lens vesicle [6], We previously reported that glycogen ap peared in the posterior portion of the lens ves icle at stage 15 [19], Therefore, the distribu tion of HSP28 in the lens vesicle at stage 15 was similar to that of glycogen rather than that of aB-crystallin. In the present study, HSP28 appeared in the anterior lens epithelium at stage 19.…”
Section: Hsp In the Lenses Of Human Embryosmentioning
confidence: 85%